Implementing Student Teams Achievement Divisions (STAD) for Increasing Students’ Speaking Skill - Muhammad Raihan; Leil Badrah Zaki (Universitas Pahlawan Tuanku Tambusai, 2023)
Students Teams Achievement Divisions (STAD) implemented to improve students' especially in English-speaking classes. Classroom Action Research (CAR) was used to solve the problem faced by the students at one of public high school in grade 9 of the second semester in one of school in Southern Thailand. The researchers as teachers observed 21 science students through evaluation in the English class. The researchers compared pre-test and post-test to obtain data and found out whether the strategy was effective in improving students speaking skills. The data was collected through four-part cycle involved (1) Planning, (2) Action, (3) Observing, and (4) Reflecting. The results revealed the improvement of students speaking skills in pre-test and post-test. The students achieved 58.09 for the average score of pre-tests which is categorized poor. After implementing Students Teams Achievement Divisions (STAD) activities, the students’ average scores improved. The post-test gained 73,14 with a great improvement in several aspects such as Pronunciation was 24.00% and followed by Performance Skill was 15,04% improvement. The evidence indicates that students responded positively to Students Teams Achievement Divisions (STAD) method especially in the quizzes. The findings concluded that Students Teams Achievement Divisions (STAD) have impacted student motivation toward learning and improved their speaking skills.